The migratory Mute Swan Cygnus olor population in East Asia - Meng, Fanjuan; Chen, Liding; Zhang, Beixi; Li, Chang; Zhao, Gerelt; Batbayar, Nyambayar; Natsagdorj, Tseveenmyadag; Damba, Iderbat; Liu, Songtao; Wood, Kevin A.; Cao, Lei; Fox, Anthony D. (Wildfowl, 2020)
Until recently, almost nothing was known about the migration routes, flyway structure and population status of the Mute Swan Cygnus olor in East Asia. Here, we use a combination of GPS telemetry data, collar resightings, published literature and expert advice to update existing knowledge of its summer and winter distribution in the region, and to provide a preliminary description of the swansâ€™ migration and habitat use. Three flyway units were indicated for the Mute Swan in East Asia. The Eastern China-wintering unit includes swans summering along the lower Selenga River in Russia, in central Mongolia and Inner Mongolia in China, which winter on the coast of eastern China, where 403 swans were counted in 2014/15, but where less than 30 have been counted in very recent years. In the absence of better data, we conservatively estimate this Chinese-wintering group at 400 birds. Mute Swans in the Korean-wintering unit are individuals that winter along the Korean Peninsula and summer in Inner Mongolia (China) and the Amur region (on the border of China and Russia); they are poorly covered by the mid-winter waterbird counts in South Korea and we have no knowledge of numbers wintering in North Korea. Finally, mid-winter counts of the introduced and sedentary population of Mute Swans in Japan have amounted to c. 240 birds in the last five years. We therefore suspect that there are likely c. 1,000 Mute Swans in Far East Asia, but await improved coverage throughout the entire wintering grounds to provide a better population estimate, with the species confirmed as one of the poorer known of the migratory waterbirds in the region. A single GPS-tagged Mute Swan tracked successfully provided detailed information on its migration routes, timing of migration and habitat use (almost exclusively waterbodies) over four complete migration episodes. It summered at Dalai Lake, China, used three stopover sites (on the borders of Russia and North Korea, in North Korea, and Baicheng City in China) during spring and autumn migration, and showed site fidelity to summer, winter and stopover sites. Combined count data and GPS data suggested that Mute Swans mostly occur within protected areas throughout the year. However, further research is required to establish the true distribution and abundance of this small and scattered species within these three flyways in East Asia, as well as to confirm its population structure and migration routes.Â 